Malaysian license plate number detection based on sobel vertical edge algorithm / Siti Nor Azimah Ibrahim - Ibrahim, Siti Nor Azimah (Faculty of Computer and Mathematical Sciences, 2007)
Transportation is the most important in daily live. Nowadays people use verity of transportation either on the road, air or water. Recently, in Malaysia the use of vehicles has been increased because of the population growth and human needs. Furthermore, Malaysian had been produced many types of vehicles to be used. Therefore, the control of vehicles is become more complex and much more difficult to solve. A License Plate Recognition (LPR) System is one kind of Intelligent Transport systems and is of considerable interest because of its potential applications to areas such as highway electronic toll collection, Traffic Monitoring System and so on. The system captures the images of the vehicles with a digital camera. An algorithm for the detection of license plate has been designed and an algorithm for filter the detected edge is proposed for future process which is plate number extraction This project describes the method used by a computer to convert digital images of vehicles license plate into electronic text. Sobel Vertical Edge Algorithm approach will be used in order to detect the license plate number fi-om digital image as well as some experimental result to filter the detected edge of license plate successfully.